FLT3: A narrative review - Nikhil M Kumar; Shrinidhi Nathany; Anusha Swaminathan; Chitresh Yadav; Akriti Kothari; Paritosh Garg; Neha Panda-Rastogi; Vikas Dua; Arun Danewa; Rahul Bhargava (Cancer Research, Statistics, and Treatment)
The adoption of next-generation sequencing (NGS) has unraveled myriad genomic alterations across all myeloid malignancies, changing not only the prognostic paradigm but also the therapeutic paradigm. Many alterations have been incorporated in the classification and categorization of these neoplasia by the World Health Organization (WHO) in its 5th edition of the classification for hematolymphoid neoplasms, as well as international consensus classifications. One among them is the Feline McDonough sarcoma tyrosine kinase 3 (FLT3). Since time immemorial, many studies have been conducted to understand the clinico-pathologic features, including responses to small molecules developed for the same. A lot of emphasis has been placed on the allele ratio and mutation burden, the concept of which has now been abolished owing to evidence-based medicine validating no differences in outcomes between high- and low-allele ratio diseases. The advent of FLT3 inhibitors has changed the therapeutic landscape of FLT3-mutated cases and is categorized as intermediate risk. Despite remarkable development and understanding of the disease, a lot remains to be understood. This is a narrative review elucidating the biology, alterations, clinico-pathologic features, detection methods, therapeutic strategies, prognosis, and newer developments in the context of FLT3. We searched PubMed, Embase, and Scopus databases using the keywords FLT3, tyrosine kinase inhibitors (TKI), acute myeloid leukemia (AML), and internal tandem duplications (ITD). No formal inclusion or exclusion criteria were set, as this is a narrative review. A total of 59 articles were reviewed to construct this article.